CHD1 assumes a central role during follicle development. - Papantonis, A; Tsatsarounos, S; Vanden Broeck, J; Lecanidou, R (2008)
During Bombyx mori follicle development, fine-tuning of chorion gene expression is under the control of bidirectional promoters. In this work, we show that the silkmoth chromo-helicase/ATPase-DNA binding protein 1 (CHD1) ortholog is responsible for repositioning of nucleosomes on chorion promoters, where the factor binds specifically. Chorion genes, occupying a single chromosomal locus, rely on an almost identical set of cis elements for their differential expression. As a direct consequence of remodeling, interaction of C/EBP and TFIID with promoter elements is facilitated and ultimately leads to initiation of transcription. Appending of methylation marks to H3K4 in a temporal-specific manner is dependent on CHD1 binding to cognate cis elements and signifies gene activation. Overall, CHD1 is a critical factor for proper development of the follicular epithelium in terms of whole-cell chromatin arrangement.